Análise das intervenções verbais de um professor de basquetebol a partir dos referenciais da pedagogia do esporte - Pinto, Túlio César Marques (Brasil, 2024)
The present study aims to analyze, based on sport pedagogy references, the pedagogical nature of the coach's interventions during basketball training. The research adopts a quantitative-qualitative approach, combining frequency survey of coach interventions with qualitative interpretation to attribute meaning to quantitative data. Furthermore, the study is exploratory in nature, seeking to contribute to the understanding of a topic that has been little explored. The research subject/participant is a school basketball coach with extensive experience and training in Physical Education. This trainer was chosen out of convenience, as the researcher works at the same educational institution. The research results highlight the significant role of coaches as facilitators of sports learning, going beyond the transmission of skills and strategies. They play an educational role by shaping values, promoting teamwork and assisting in the physical and psychological development of athletes. In summary, the study highlights the importance of the coach's role as an educator in the sporting context and provides insights into the emphasis given to verbal interventions in basketball training based on sport pedagogy references.